An Experimental and Numerical Investigation on the Initiation and Interaction of Double Cracks in Rocks under Hydromechanical Coupling - Jie Mei; Wanzhi Zhang (Advances in Materials Science and Engineering)
The growth of double cracks is the main factor leading to progressive rock failure under hydromechanical coupling. The initiation modes and interaction behaviors of double cracks were investigated by using laboratory tests, and the influences of water pressure were analyzed. The maximum energy release rate criterion was modified to determine the crack growth characteristics. A numerical model was established and then verified by the test results. Based on the simulation, the distribution of stress fields and key fracture parameters of double cracks was investigated. Then, initiation characteristics and interaction behaviors of parallel and nonparallel cracks were quantitatively analyzed. The results indicate that the increase in water pressure leads to the crack initiation being inclined to the original surfaces and the growth length along the crack fronts tending to be uniform; the small tensile stress zones are formed close to the crack tips, and significant compressive stress zones are formed at both sides of the crack surfaces; stress superposition and interaction occur when crack spacing is less than 2.5a; the interactive weakening effect is mainly present in the inner side (rock bridge zone) of cracks, while a certain degree of interactive enhancement effect exhibits in the outer sides; the cracks are much easier to initiate at the outer wing cracks when the spacing is less than the critical length (0.5a); and cracks with a dip angle of 45° are much easier to initiate at the endpoints of long axis. The research results provide certain theoretical guidance for the safety assessment of underground engineering.